THE APPLICATION OF SAFINDA METHOD IN TRANSLATION LEARNING AL-QUR'AN IN STUDENTS IN FATTAHUL MULUK PAPUA - Muhyidin, Syaiful; Abubakar, Achmad; Umar, M. Sabir; Munir, Munir (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This paper elaborates on the application of the Safinda method in learning the translation of al-Quran for students at IAIN Fattahul Muluk Papua. This type is qualitative research, the research approach is a phenomenological perspective and a descriptive analysis approach, and data sources are primary data and secondary data, data collection techniques through observation, interviews, and documentation. The research instrument, namely, the researcher as a key instrument, observation guide, interview guide and documentation reference, data processing and analysis techniques namely data reduction, data presentation, conclusion and verification, data validity testing, namely triangulation techniques, checking the correctness of the information, discussing and consulting data, and extending research time. The results of the study found that the application of the Safinda method in learning the translation of al-Quran to students at IAIN Fattahul Muluk Papua was carried out by (a) paying attention to class management which included classroom arrangement and student management before entering preliminary activities; (b) in the introductory activity, the lecturer starts learning effectively and pleasantly by providing motivation to students; (c) the core activities are carried out through reading activities, aural-oral activities, and memorizing activities are all carried out classically and individually, namely the lecturer reads word for word followed by students, lecturers and students read word for word, students read word for word, the lecturer interprets it, the students interpret all the verses that have been read together, the students read one by one, then the lecturer gives the opportunity to students who do not understand to ask questions, and finally the lecturer explains all the verses that have been studied together.